Cryo-EM structure of a 40 kDa SAM-IV riboswitch RNA at 3.7 Å resolution - Kaiming Zhang (Nature Portfolio, 2019)
The conformational heterogeneity of RNA molecules makes their structure determination by X-ray crystallography and NMR challenging. Here the authors show that RNA structures can be solved by cryo-EM and present the structures of a 40 kDa SAM-IV riboswitch in the apo form and bound to its ligand S-adenosylmethionine.